Structural insight into the distinct regulatory mechanism of the HEPN–MNT toxin-antitoxin system in Legionella pneumophila - Chenglong Jin; Cha-Hee Jeon; Heung Wan Kim; Jin Mo Kang; Yuri Choi; Sung-Min Kang; Hyung Ho Lee; Do-Hee Kim; Byung Woo Han; Bong-Jin Lee (Nature Communications)
Abstract HEPN–MNT, a type VII TA module, comprises the HEPN toxin and the MNT antitoxin, which acts as a nucleotidyltransferase that transfers the NMP moiety to the corresponding HEPN toxin, thereby interfering with its toxicity. Here, we report crystal structures of the Legionella pneumophila HEPN–MNT module, including HEPN, AMPylated HEPN, MNT, and the HEPN–MNT complex. Our structural analysis and biochemical assays, suggest that HEPN is a metal-dependent RNase and identify its active site residues. We also elucidate the oligomeric state of HEPN in solution. Interestingly, L. pneumophila MNT, which lacks a long C-terminal α4 helix, controls the toxicity of HEPN toxin via a distinct binding mode with HEPN. Finally, we propose a comprehensive regulatory mechanism of the L. pneumophila HEPN–MNT module based on structural and functional studies. These results provide insight into the type VII HEPN–MNT TA system.